EL DESAFÍO DE LA INNOVACIÓN AL INTERIOR DE LAS PYMES EN COLOMBIA Y COMO SOLUCIONARLOS MEDIANTE HERRAMIENTAS PRÁCTICAS - Ricardo Villalba; Elkin Darío Morales Gil (Revista Ingeniería, Matemáticas y Ciencias de la Información, 2019)
In the following article we will talk about the main PYMES ́s challenges in Colombia, by means of a harvest of informationthrough surveys and data collected by government agencies, besides, some newspapers that investigate about the actualsituation of PYMES in Colombia. After this, we will present some solutions applicable and efficient by PYMES.